المواجهة التشريعية لإتلاف المكونات المادية للنظام الآلي لمعالجة المعطيات - الهيتي، محمد حماد مرهج (جامعة الشارقة, 2008)
يهدف البحث إلى بيان ضرورة المواجهة التشريعية بنص خاص عند تعرض المكونات المادية للنظام الآلي لمعالجة المعطيات للإتلاف لعدم إمكان تطبيق نصوص جريمة الإتلاف للصعوبات التي تعترض ذلك. وقد قسم البحث إلى خمسة مباحث اختص الأول منها ببيان معنى النظام الآلي لمعالجة المعطيات طبقاً لموقف الفقه ومجلس الشيوخ الفرنسيين في حين اختص المبحث الثاني منها بضرورة تجريم وتحديد مدلول النظام الآلي لمعالجة المعطيات والذي تظهر أهميته في نطاق جريمة الإتلاف بشكل خاص. أما المبحث الثالث فقد اختص ببيان ضرورات النص الخاص عند إتلاف المكونات المادية المرتبطة بالنظام الآلي أو الداخلة في تكوينه. أما المبحث الرابع فقد اختص في توضيح ضرورات المواجهة التشريعية بنص الخاص عند إتلاف المكونات المادية بقصد إتلاف المكونات غير المادية التي تتضمنها لما تشكله من أهمية ولما يشكل الاعتداء عليها من خطر يهدد عمل النظام وأدائه لوظائفه. بينما اختص المبحث الأخير لبيان ضرورة المواجهة التشريعية بنص خاص لتحقق إتلاف المكونات المادية بوسائل غير مادية أو إلكترونية لا تؤثر على المكونات المادية بحيث تحتفظ بتماسك كيانها المادي وتكامل جزئياتها إنما ينصب تأثيرها على وظائفها فحسب وختمنا البحث باقتراح نص جزائي يتكون من أربع مواد يمكن الاسترشاد بها في تجريم إتلاف النظام الآلي لمعالجة المعطيات. This research aims to clarifying or explaining the justifications which we can rely on. the research also demonstrates the need for special legislation, when components of the system that deal with the destroyed or disrupted data. The research is divided into five chapters:- The first chapter is pertaining to clarify the meaning of the automatic data processing system according to opinions of Jurists and franc senate point of view. The second chapter, after the discussion of the Jurists point of view which results issue from the definition of the senate upon damaging or break down of the automatic data processing system crime. The third chapter is assigned to explaining the necessity of the special statute when the material element is included or enter in the forming of the processing system or connected whit it, when the components of the system is damaged. The fourth chapter is assigned to explain the necessity of the special statute when the material elements are damaged with the intent to damaging soft ware which includes (program, information and data) which are un materiality nature. While in the last chapter we discussed the damaging the material element of the automatic data processing system by non-material method such as electromagnet power which affects on the material element job and Its task or like Magneto-ray guidance affecting the hardware and then affecting the functions with coherence and complementarily of its physical parts. At the end we suggested fourth artecals which we can applied at such cases.
Keywords: جريمة الاتلاف -- نظم المعلومات القانونية -- معاجلة البيانات -- الحاسبات الإلكترونية -- اتلاف أجهزة معالجة البيانات -- الجريمة و المجرمون -- القانون الجنائي -- قانون العقوبات -- أمن المعلومات